High-quality photoelectric glass material with anti-dazzle function as well as preparation method and application of high-quality photoelectric glass material
Through the photoelectric glass materials processed by specific components and processes, the existing photoelectric glass materials have solved the problems of poor anti-glare effects and inconsistent mechanical properties, and achieved high transmittance, low thermal expansion coefficient and high bending intensity, which are suitable for high-end photoelectric detection and precision optical systems.
Patent Information
- Application Number
- CN202510010764.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-08
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing photoelectric glass materials have poor performance in anti-glare functions, complex coating manufacturing and poor durability, high and uneven chemical reinforcement treatment costs, inconsistent mechanical properties, and there is a gap between domestic production and international levels.
Through a combination of glass compositions of specific component ratios, including SiO2, Bi2O3, PbO, In2O3, AgO, SnO2, Li2O, Na2O, K2O, B2O3, Al2O3, ZrO2, MgO, CaO, CeO2 and Sb2O3, combined with high-temperature melting, mechanical stirring, annealing and other processes, a photoelectric glass with a light absorption layer is formed, and chemically strengthened treatment is performed to improve performance.
It achieves excellent spectral transmittance, anti-halo and anti-crosstalk performance, good thermal performance and mechanical strength, meets the needs of high-end applications, and becomes an ideal material for optical input windows and protective covers.
Smart Images

Figure CN119774875A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of glass, and in particular to a high-quality photoelectric glass material with an anti-glare function, a preparation method and application thereof. Background Art
[0002] Any discussion of the prior art throughout the specification should not be considered as an admission that such prior art is widely known or forms part of the common general knowledge in the field.
[0003] Photoelectric glass is an advanced special glass material that can form a highly efficient absorption layer with a non-reflective interface around the effective area through substrate generation technology. Therefore, it has become the preferred optical input window material in high-end photoelectric detection and precision optical systems, and is a key material for capacitive touch screens and protective cover glass. Photoelectric glass is widely used in various fields such as smartphones, tablets, IPADs, industrial control displays, aerospace, solar thermal photovoltaic power generation, and automotive. This puts higher requirements on photoelectric glass, not only covering its spectral range and stray light absorption rate, but also including anti-drop, anti-scratch, pressure resistance, high temperature resistance, LCD protection and decorative functions.
[0004] However, there are many problems with the high-performance photovoltaic glass currently on the market. First, the inherent brittleness and fragility of glass makes it easy to be damaged in applications such as protective cover plates. To overcome this problem, chemical strengthening technology is applied to the production of high-performance photovoltaic glass materials. Although this technology can significantly reduce the length and depth of microcracks on the surface of the glass, and sometimes even completely eliminate smaller microcracks, there are still some problems. For example, chemical strengthening can only treat cracks on the surface of the glass and cannot improve the structural defects inside the glass. In addition, the chemical strengthening process is complicated and costly, and in some cases, the treatment effect may be uneven, resulting in inconsistent mechanical properties of the glass.
[0005] Especially in terms of anti-glare function, existing optoelectronic glass materials have obvious shortcomings, especially in strong light environments, such as when using smart devices outdoors, the anti-glare effect of existing technologies is not ideal, affecting user experience. At present, the anti-glare function is usually achieved by adding a specific coating to the glass surface or using a nanostructure. Although this surface treatment can significantly reduce the intensity of reflected light and thus reduce glare, there are still some problems. First, the manufacturing process of these coatings and nanostructures is complex and costly. In addition, there are problems with the durability and long-term stability of the coating, which is easy to wear or fall off during use, resulting in a weakened anti-glare effect. Furthermore, the presence of the coating may affect the light transmittance and other optical properties of the glass, resulting in limited improvement in overall performance.
[0006] In addition, although China is the world's leading producer of PCs, tablets and smartphones, the production of high-performance optoelectronic glass requires a large amount of capital investment and high technology level, and the current domestic market mainly relies on imports. Existing domestic companies such as Rainbow, Xuhong, CSG, and CNBM, although they have a small amount of production, the product quality is still far behind the international leading level. This situation restricts the development and technological innovation of the domestic high-performance optoelectronic glass industry, and more capital and technology investment is urgently needed. Faced with this situation, the research and development and manufacture of more advanced optoelectronic glass has become an urgent need. This requires not only more sophisticated and efficient chemical strengthening technology, but also in-depth research on the structure and properties of the material itself, so as to develop new materials that can meet the growing application needs.
[0007] The purpose of the present invention is to overcome or improve at least one disadvantage of the prior art, or to provide a useful alternative. Unless the context clearly requires otherwise, throughout the specification and claims, the words "include", "comprises", etc. should be interpreted from an inclusive perspective rather than an exclusive or exhaustive perspective; that is, from the perspective of "including, but not limited to". Summary of the invention
[0008] The purpose of the present invention is to provide a high-quality optoelectronic glass material with anti-glare function, and a preparation method and application thereof. The optoelectronic glass material provided by the present invention has excellent spectral transmittance, excellent stray light elimination and anti-crosstalk performance after high-temperature reduction treatment, good thermal properties, excellent glass internal quality, and high bending strength after chemical strengthening. It can achieve comprehensive improvements in optical properties, mechanical strength and environmental adaptability, and can fully meet high-end application requirements, which makes it an ideal choice for optical input window materials in high-end optoelectronic detection and precision optical systems, key materials for capacitive touch screens, or protective cover glass.
[0009] In order to achieve the above object, the present invention provides the following technical solutions: In a first aspect, a glass composition is provided, comprising or consisting of the following components, in mass percentage: 45-55% SiO2, 0.1-3% Bi2O3, 0-2% PbO, 0.1-3% In2O3, 0-3% AgO, 0.1-2% SnO2, 1-5% Li2O, 8-16% Na2O, 0-1% K2O, 0-4% B2O3, 10-18% Al2O3, 1-8% ZrO2, 1-3% MgO, 1-4% CaO, 0-1% CeO2 and 0-2% Sb2O3.
[0010] In the present invention, SiO2 exists in the glass structure in the form of [SiO4] tetrahedron, which can reduce the thermal expansion coefficient and improve the thermal stability, heat resistance, chemical stability and mechanical strength of the glass. Al2O3 is a glass intermediate oxide in the present invention. Most of the Al2O3 in the glass structure is 3+ Both can form [AlO4] tetrahedral structure. The volume of [AlO4] in glass is 41 cm 3 / mol, the volume of [SiO4] is 27 cm 3 / mol, [AlO4] is 52% larger in volume than [SiO4], so [AlO4] will lead to an increase in glass voids, which is beneficial to improving ion exchange efficiency and making the glass material have excellent chemical strengthening properties. However, excessive SiO2 and Al2O3 will inevitably increase the melting temperature and viscosity, which will cause a heavy burden on the glass melting and clarification process. B2O3 is a glass-forming oxide in the present invention, with boron oxide triangles [BO3] and boron oxide tetrahedrons [BO4] as structural units. In silicate glass, B can partially replace Si to form a network structure. In addition, B2O3 has a fluxing effect in glass, which can reduce the high-temperature viscosity of glass, save costs, and facilitate production. At the same time, it improves the thermal stability and chemical stability of glass, increases the refractive index of glass, and improves the gloss of glass. Therefore, in the high-quality optoelectronic glass material with anti-glare function of the present invention, the content of SiO2 is in the range of 45-55%, the content of Al2O3 is in the range of 10-18%, and the content of B2O3 is in the range of 0-4% by mass percentage.
[0011] In some embodiments of the present invention, the content of SiO2, measured by mass percentage, can be selected from the following ranges or values within the following ranges: 44.9-49.0%, 44.9-52.0%, 44.9-53.0%, 44.9-55.0%, 45.0-55.0%, 49.0-52.0%, 49.0-53.0%, 49.0-55.0%, 52.0-53.0%, 52.0-55.0%, 53.0-55.0%, 53.5-55.0%, 54.0-55.0%, and the like.
[0012] In some embodiments of the present invention, the content of Al2O3, in percentage by mass, can be selected from the following ranges or values within the following ranges: 10-11.0%, 10-11.5%, 10-11.7%, 10-12.8%, 10-14.0%, 10-16.0%, 10-18.0%, 11.7-12.8%, 11.7-14.0%, 11.7-16.0%, 11.7-18.0%, 12.8-14.0%, 12.8-16.0%, 12.8-18.0%, 14.0-16.0%, 14.0-18.0%, 16.0-18.0%, and the like.
[0013] In some embodiments of the present invention, the content of B2O3, in percentage by mass, can be selected from the following ranges or values within the following ranges: 0, 0-1.0%, 0-1.3%, 0-1.7%, 0-3.0%, 0-4.0%, 1.0-1.3%, 1.0-1.7%, 1.0-3.0%, 1.0-4.0%, 1.3-1.7%, 1.3-3.0%, 1.3-4.0%, 1.4-1.7%, 1.7-2.0%, 1.7-2.5%, 1.7-2.9%, 1.7-3.0%, 1.7-4.0%, 3.0-4.0%, and the like.
[0014] In the present invention, Bi2O3 is an important additive in the present invention. Bi2O3 can be reduced to the metallic state of bismuth, i.e., black bismuth, in a high-temperature reducing atmosphere. Based on the component design and physical and chemical treatment of the present invention, the reduction of bismuth can be locally controlled at the periphery of the effective light-transmitting area of the glass, thereby generating a light-absorbing layer with high light absorption capacity by in-situ reaction on the glass substrate. This layer can effectively absorb stray light passing through the glass and reduce the halo effect. However, the amount of Bi2O3 introduced needs to be precisely controlled to avoid the reduction of the chemical stability of the glass and the serious corrosion of the melting container due to excessive addition. Therefore, in the high-quality optoelectronic glass material with anti-glare function of the present invention, the content of Bi2O3 is in the range of 0.1-3% by mass.
[0015] In some embodiments of the present invention, the content of Bi2O3, measured by mass percentage, can be selected from the following ranges or values within the following ranges: 0.1-1.0%, 0.1-0.9%, 0.1-0.8%, 0.1-0.7%, 0.1-0.6%, 0.1-0.5%, 0.1-0.4%, 0.1-0.3%, 0.1-0.2%, 0.1-2.4%, 0.1-3.0%, 1.0-2.4%, 1.0-3.0%, 2.4-3.0%, and the like.
[0016] In the present invention, PbO is an important additive. As a network-external oxide, it not only increases the thermal expansion coefficient and refractive index of the glass, but also reduces the melting temperature, so that the glass has better optical properties by taking away oxygen ions in the Si-O network and causing Si-O network disconnection to form non-bridging oxygen. In the present invention, the content of PbO is in the range of 0-2.0% by mass. In some embodiments of the present invention, the content of PbO is selected from the following ranges or values in the following ranges, measured by mass percentage: 0, 0-0.1%, 0-0.2%, 0-0.3%, 0-0.4%, 0-0.5%, 0-1.0%, 0-1.5%, 0-2.0%, 0.5-1.0%, 0.5-1.5%, 0.5-2.0%, 1.0-1.4%, 1.0-1.5%, 1.0-2.0%, 1.5-2.0%, 1.6-2.0%, 1.7-2.0%, 1.8-2.0%, 1.9-2.0%, and the like.
[0017] In the present invention, AgO is an important additive in optoelectronic glass, and is usually introduced into the glass using silver nitrate. Silver nitrate will precipitate colloidal particles of silver during the glass melting process, and the glass will appear light yellow after heating and reduction. However, too high or too low an AgO content will have an adverse effect on the performance of the glass. Too high an AgO content will result in too many silver particles precipitated in the glass, significantly reducing the light transmittance of the glass, affecting its transparency and color. On the contrary, too low an AgO content is not enough to form enough silver particles, and the optoelectronic properties of the glass cannot be significantly improved, affecting its effect in optoelectronic applications. At the same time, the addition of an appropriate amount of AgO can effectively improve the thermal conductivity and mechanical properties of the glass. Therefore, the content of AgO needs to be precisely controlled to balance the light transmittance, light absorption capacity and optoelectronic properties of the glass. In the present invention, the content of AgO ranges from 0 to 3.0% by mass. In some embodiments of the present invention, the content of AgO is selected from the following ranges or values within the following ranges, measured by mass percentage: 0, 0-0.5%, 0-1.0%, 0-1.2%, 0-2.0%, 0.5-1.0%, 0.5-1.2%, 0.5-2.0%, 0.6-1.0%, 1.0-1.2%, 1.0-2.0%, 1.1-1.2%, 1.2-1.3%, 1.2-1.4%, 1.2-1.5%, 1.2-1.6%, 1.2-1.7%, 1.2-1.8%, 1.2-1.9%, 1.2-2.0%, and the like.
[0018] In some embodiments of the present invention, AgO and PbO are not simultaneously 0. In some embodiments of the present invention, the sum of the contents of AgO and PbO is 0.5-3.5%, preferably 1-3.2%, more preferably 1-2% or 2.8-3.2%, by mass percentage.
[0019] In the present invention, the addition of In2O3 can improve the thermal conductivity and mechanical properties of the glass material. When the indium content is low, the thermal stability and heat resistance of the glass can be effectively improved, and an appropriate increase in the indium content can increase the density and refractive index of the glass. However, excessive In2O3 content can cause severe discoloration of the glass. Therefore, the present invention can improve the performance of the glass while maintaining the stability of its optical properties by controlling the addition amount of In2O3. In the present invention, the content range of In2O3 is 0.1-3.0% by mass. In some embodiments of the present invention, the content of In2O3, in terms of mass percentage, is selected from the following ranges or values within the following ranges: 0.1-1.0%, 0.1-1.5%, 0.1-2.0%, 0.1-2.8%, 0.1-3.0%, 1.0-1.5%, 1.0-2.0%, 1.0-2.8%, 1.0-3.0%, 1.5-2.0%, 1.5-2.8%, 1.5-3.0%, 1.6-2.0%, 1.7-2.0%, 1.8-2.0%, 1.9-2.0%, 2.0-2.1%, 2.0-2.2%, 2.0-2.3%, 2.0-2.4%, 2.0-2.5%, 2.0-2.7%, 2.0-2.8%, 2.0-3.0%, 2.8-3.0%, and the like.
[0020] In the present invention, the introduction of SnO2 can enhance the transparency, heat resistance and light scattering ability of the glass. At the same time, during the melting process of the glass, SnO2 will react with other glass components to form hard crystals. These crystals are dispersed in the glass, which can increase the hardness and flexural strength of the glass and reduce the possibility of scratches on the glass surface. In the present invention, the content of SnO2 is in the range of 0.1-2.0% by mass. In some embodiments of the present invention, the content of SnO2, measured by mass percentage, is selected from the following ranges or values within the following ranges: 0.1-0.5%, 0.1-0.8%, 0.1-1.0%, 0.1-1.3%, 0.1-2.0%, 0.5-0.8%, 0.5-1.0%, 0.5-1.3%, 0.5-2.0%, 0.8-1.0%, 0.9-1.0%, 0.8-1.3%, 0.8-2.0%, 1.0-1.1%, 1.0-1.2%, 1.0-1.3%, 1.0-2.0%, 1.3-2.0%, and the like.
[0021] In some embodiments of the present invention, the content of In2O3 is greater than the content of SnO2. In some embodiments, the content of In2O3 is 2-15 times, preferably 2-10 times, more preferably 2-5 times, 2-3.5 times or 2-3 times the content of SnO2 by mass percentage. In some embodiments, the sum of the contents of In2O3 and SnO2 by mass percentage is 1-4.5%, preferably 2-4.3%, more preferably 2.5-4%, and most preferably 3-3.6%.
[0022] In some embodiments of the present invention, the sum of the contents of PbO, Bi2O3 and SnO2 is 1.5-6.5% by mass, preferably 1.8-5%, more preferably 1.8-3.5%, and most preferably 2.5-3.5%.
[0023] In the present invention, Li2O, Na2O and K2O are the network outer oxides of the glass. The alkali metal ions are easy to move and diffuse in the glass, which can reduce the viscosity of the glass during high-temperature melting and make the glass easy to melt. They are good fluxing agents. However, if the content is too high, it will affect the chemical stability of the glass and have a series of effects on the forming process. In addition, Li + and Na + Ions are necessary ion exchange components. When Li2O and Na2O are introduced together, two-step chemical strengthening is used, which is conducive to forming a deeper ion exchange depth (DOL) and surface compressive stress (CS). As a result, the strengthened photovoltaic glass has higher strength and impact resistance. Therefore, in the high-quality photovoltaic glass material with anti-glare function of the present invention, the content of Li2O is in the range of 1-5%, the content of Na2O is in the range of 8-16%, and the content of K2O is in the range of 0-1%, by mass percentage.
[0024] In some embodiments of the present invention, the content of Li2O can be selected from the following ranges or values within the following ranges, measured by mass percentage: 1.0-2.0%, 1.0-3.0%, 1.0-5.0%, 1.1-2.0%, 1.5-2.0%, 1.8-2.0%, 2.0-3.0%, 2.0-5.0%, 2.0-2.9%, 2.0-2.8%, 2.0-2.5%, 2.0-2.3%, 3.0-5.0%, and the like.
[0025] In some embodiments of the present invention, the content of Na2O can be selected from the following ranges or values in the following ranges, by mass percentage: 8.0-10.7%, 8.0-12.6%, 8.0-15.0%, 8.0-15.2%, 8.0-16.0%, 8.1-10.7%, 8.5-10.7%, 8.9-10.7%, 9.1-10.7%, 9.5-10.7%, 10-10.7%, 10.5-10.7%, 1 0.7-12.6%, 10.7-15.0%, 10.7-15.2%, 10.7-16.0%, 10.7-12.5%, 10.7-12.0%, 10.7-11.9%, 10.7-11.5%, 10.7-11.0%, 12.6-15.0%, 12.6-15.2%, 12.6-16.0%, 15.0-15.2%, 15.0-16.0%, 15.2-16.0%, etc.
[0026] In some embodiments of the present invention, the content of KO can be selected from the following ranges or values within the following ranges, measured by mass percentage: 0, 0-0.1%, 0-0.5%, 0-0.8%, 0-1.0%, 0.1-0.5%, 0.1-0.8%, 0.1-1.0%, 0.2-1.0%, 0.2-0.8%, 0.3-0.8%, 0.4-0.8%, 0.6-0.8%, 0.7-0.8%, 0.8-0.9%, 0.5-0.8%, 0.5-1.0%, 0.8-1.0%, and the like.
[0027] In the present invention, ZrO2 is a glass intermediate oxide, which has the effect of improving chemical stability and preventing the exposure of alkali metal and alkaline earth metal ions. It is also an important component for improving the tensile elastic modulus, and is very helpful for improving the hardness of glass after chemical strengthening. Therefore, in the high-quality optoelectronic glass material with anti-glare function of the present invention, the content of ZrO2 is in the range of 1-8% by mass.
[0028] In some embodiments of the present invention, the content of ZrO2 can be selected from the following ranges or values within the following ranges, measured by mass percentage: 1.0-2.5%, 1.0-2.9%, 1.0-4.6%, 1.0-7.0%, 1.0-8.0%, 1.1-2.5%, 1.5-2.5%, 1.6-2.5%, 1.8-2.5%, 2.0-2.5%, 2.1-2.5%, 2.3-2.5%, 2.5-2.9%, 2.5-4. 6%, 2.5-7.0%, 2.5-8.0%, 2.9-4.6%, 2.9-7.0%, 2.9-8.0%, 4.6-7.0%, 4.6-8.0%, 4.7-8.0%, 5.0-8.0%, 5.5-8.0%, 6.0-8.0%, 6.5-8.0%, 7.0-8.0%, 7.1-8.0%, 7.3-8.0%, 7.5-8.0%, 7.6-8.0%, 7.8-8.0%, etc.
[0029] In the present invention, the addition of MgO and CaO can greatly reduce the phase separation tendency of the glass. At the same time, adding MgO on the basis of alkali-aluminosilicate glass can help the glass break the network and promote the formation of multi-rings in the network structure, including ternary rings, quaternary rings, pentacyclic rings and hexacyclic rings, etc., which can not only meet the integrity of the glass connection, but also help to create gaps between glass structural units, create exchange channels for ion exchange, and help to improve the depth of the compressive stress layer (DOL) after chemical strengthening, thereby improving the bending strength and overall impact resistance of the glass. The main role of CaO in the glass of the present invention is a stabilizer, that is, to increase the chemical stability and mechanical strength of the glass. However, improper use increases the crystallization tendency of the glass and makes the glass brittle. Therefore, in the high-quality optoelectronic glass material with anti-glare function of the present invention, the content of MgO is in the range of 1-3%, and the content of CaO is in the range of 1-4% by mass.
[0030] In some embodiments of the present invention, the content of MgO, in terms of mass percentage, may be selected from the following ranges or values within the following ranges: 1.0-1.2%, 1.0-2.2%, 1.0-3.0%, 1.2-2.2%, 1.2-3.0%, 2.2-3.0%, 2.3-3.0%, 2.5-3.0%, 2.8-3.0%, and the like.
[0031] In some embodiments of the present invention, the content of CaO, in terms of mass percentage, can be selected from the following ranges or values within the following ranges: 1.0-2.0%, 1.0-3.0%, 1.0-4.0%, 2.0-2.9%, 2.0-2.3%, 2.0-2.5%, 2.0-3.0%, 2.0-4.0%, 3.0-4.0%, 3.1-4.0%, 3.5-4.0%, 3.8-4.0%, and the like.
[0032] CeO2 and Sb2O3 are used as glass clarifiers in the present invention. CeO2 is a variable valence oxide, which mainly removes bubbles from the glass liquid by being reduced at high temperature (losing oxygen) and oxidized at low temperature (obtaining oxygen). The process of decomposing and releasing oxygen at high temperature will increase the gas partial pressure in the bubbles, increase the volume of the bubbles, thereby accelerating the bubbles to rise and be removed from the molten glass. In addition, the released oxygen can also participate in the oxidation reaction in the molten glass, which helps to eliminate some impurities with strong reducibility and improve the optical properties and chemical stability of the glass. Sb2O3 can remove or reduce impurities in the glass through its redox ability, and also has the effect of inhibiting the formation of bubbles, thereby improving the transparency and purity of the glass. Therefore, in the high-quality optoelectronic glass material with anti-glare function of the present invention, the content of CeO2 is in the range of 0-1%, and the content of Sb2O3 is in the range of 0-2% by mass percentage.
[0033] In some embodiments of the present invention, the content of CeO2, in terms of mass percentage, can be selected from the following ranges or values within the following ranges: 0, 0-0.1%, 0-0.3%, 0-1.0%, 0.1-0.3%, 0.1-1.0%, 0.2-0.3%, 0.3-1.0%, 0.3-0.9%, 0.3-0.8%, 0.3-0.7%, 0.3-0.6%, 0.3-0.5%, 0.3-0.4%, and the like.
[0034] In some embodiments of the present invention, the content of Sb2O3, in percentage by mass, can be selected from the following ranges or values within the following ranges: 0, 0-0.1%, 0-1.0%, 0-1.9%, 0-2.0%, 0.1-1.0%, 0.1-1.9%, 0.1-2.0%, 0.2-2.0%, 0.2-1.9%, 0.2-1.0%, 0.5-2.0%, 0.5-1.9%, 0.5-1.0%, 1.0-1.1%, 1.0-1.2%, 1.0-1.3%, 1.0-1.4%, 1.0-1.5%, 1.0-1.6%, 1.0-1.7%, 1.0-1.8%, 1.0-1.9%, 1.0-2.0%, 1.9-2.0%.
[0035] In some embodiments of the present invention, the contents of Sb2O3 and CeO2 are not 0 at the same time. In some embodiments, the content of Sb2O3 is not less than the content of CeO2, and preferably is higher than the content of CeO2. In some embodiments, the sum of the contents of Sb2O3 and CeO2 is 0.1-3%, preferably 1-3%, and more preferably 1.3-2.9% by mass. In some embodiments, the content of Sb2O3 is 1-3.5 times the content of CeO2, preferably 1.9-3.5 times, and more preferably 2.5-3.5 times by mass.
[0036] In a second aspect, a glass blank is provided, which is made of the high-quality optoelectronic glass material composition with anti-glare function described in the first aspect.
[0037] In an embodiment of the present invention, the preparation method of the glass blank comprises: mixing the raw materials, melting them at a high temperature of 1520-1580°C, mechanically stirring them after melting, assisting bubbling clarification, then cooling them to 1350-1500°C for molding, and annealing them at 520-580°C after molding.
[0038] In some embodiments, the raw materials may also be selected from the following materials as needed: quartz sand, bismuth oxide (or bismuth nitrate pentahydrate), red lead (or yellow lead), indium oxide, silver nitrate, tin oxide, lithium carbonate, sodium carbonate (or sodium nitrate), potassium carbonate (or potassium nitrate), boron oxide (or boric acid), aluminum hydroxide (or aluminum oxide), zirconium oxide, magnesium oxide (or basic magnesium carbonate), calcium oxide (or calcium carbonate), cerium oxide and antimony oxide.
[0039] In a third aspect of the present invention, a light-transmitting glass substrate is provided, which is prepared by mechanical processing of the glass blank according to claim 4.
[0040] In an embodiment of the present invention, the mechanical processing includes changing at least one of the physical form, surface quality and appearance of the glass blank. The physical form may be, for example, cutting the glass blank into a desired shape and size, or drilling a desired hole diameter and hole position on the glass blank. The surface quality may be, for example, polishing (e.g., mechanical polishing) to improve the smoothness and transparency of the glass blank surface, or grinding the glass edge to remove the sharp edge and improve safety. The appearance may be, for example, engraving (e.g., mechanical engraving) to make various patterns or logos on the surface of the glass blank.
[0041] In the embodiment of the present invention, the light-transmitting glass substrate has excellent spectral transmittance, and the spectral transmittance of 870nm light is ≥90.00%; it has good thermal properties, and the thermal expansion coefficient at 30-300℃ is (95-105)×10 -7 / ℃; glass transition temperature Tg≥540℃; relaxation temperature Ts≥630℃; it has excellent glass internal quality and the bubble degree meets A0 level.
[0042] In a fourth aspect of the present invention, a high-quality optoelectronic glass material with an anti-glare function is provided, which comprises the light-transmitting glass substrate described in the third aspect above, and a light-absorbing layer arranged on the surface of the light-transmitting glass substrate.
[0043] In an embodiment of the present invention, the light-transmitting glass substrate provides a light-transmitting effective area, and the light-transmitting effective area has a spectral transmittance of ≥90.00% for 870nm light, preferably ≥91%; the light-absorbing layer has a spectral transmittance of ≤1% for 870nm light, preferably ≤0.72%, and more preferably ≤0.66%. This indicates that the optoelectronic glass material of the present invention has excellent spectral transmittance and good anti-halation and anti-crosstalk performance. The high spectral transmittance of the light-transmitting area means that the glass can effectively transmit light at a specific wavelength, ensuring the efficient transmission of optoelectronic performance, which is crucial for anti-glare functions and optical applications. The low transmittance of the absorption layer indicates that the glass material can effectively absorb unnecessary light, reduce halo and crosstalk phenomena, and improve the image quality and signal clarity of the optical system.
[0044] In some embodiments of the present invention, the light absorbing layer is produced on the surface of the light-transmitting glass substrate by reducing the light-transmitting glass substrate. Preferably, the thickness of the light absorbing layer is ≥ 600 μm, preferably ≥ 650 μm.
[0045] In the present invention, the high-quality photoelectric glass material with anti-glare function has a thermal expansion coefficient of (95-105)×10 -7 / ℃; glass transition temperature Tg≥540℃, preferably ≥550℃, more preferably ≥580℃; sag temperature Ts≥630℃. This shows that the present invention has good thermal properties, the glass material of the present invention has a reasonable thermal expansion coefficient, which makes the material have stable dimensional properties when the temperature changes, avoiding material damage caused by thermal stress, the glass material of the present invention has a high glass transition temperature, which makes the glass still maintain good mechanical properties and stability at high temperatures, and has a high sag temperature, which shows that the material can still maintain its shape at high temperatures and is suitable for applications in high temperature environments.
[0046] In an embodiment of the present invention, the bubble degree of the high-quality optoelectronic glass material with anti-glare function meets the A0 level. The bubble degree A0 means that the total cross-sectional area of bubbles with a diameter of Φ≥0.05 mm is >0.03-0.10 mm 2 / 100cm 2 , which indicates that the photovoltaic glass of the present invention has excellent glass internal quality, and the low bubble degree indicates that the internal quality of the glass material is very high and there are no obvious defects, which has a positive effect on both optical properties and material strength.
[0047] In some embodiments of the present invention, the reduction treatment is performed under a reducing atmosphere, wherein the reduction treatment time is 5000-18000 min, the pressure is 0.01-0.3 MPa, and the temperature is 550-720°C.
[0048] In an embodiment of the present invention, the high-quality optoelectronic glass material with anti-glare function is chemically strengthened glass, and the chemical strengthening includes placing the glass material in a salt bath for at least one chemical ion exchange.
[0049] The temperature of each chemical ion exchange is 350-540°C, the time is 100-800 min, and the salt bath is at least one salt selected from lithium salt, sodium salt and potassium salt. Preferably, the molten salt is sodium salt or potassium salt, such as sodium nitrate or potassium nitrate.
[0050] In some embodiments of the present invention, the chemical strengthening is performed by two chemical ion exchanges, the first chemical ion exchange is performed in a salt bath of sodium salt, and the second chemical ion exchange is performed in a salt bath of potassium salt or a mixed salt of potassium salt and sodium salt.
[0051] In some embodiments of the present invention, during the chemical strengthening process, a catalyst may be added to the salt bath, and the amount of the catalyst added is 0-10 wt %, preferably 4-10%, and more preferably 5-10 wt % of the total salt mass in the salt bath.
[0052] In some embodiments of the present invention, a catalyst may be added or not added in each chemical ion exchange. For example, when performing two chemical ion exchanges, a catalyst may be added neither time nor both times, or a catalyst may be added both times, or a catalyst may be added in at least one of the two times.
[0053] In some embodiments of the present invention, the catalyst is selected from one or more of KOH, KCl, K2CO3, Rb2CO3, KH2PO4, Ca(PO3)2, K3PO4 and K2SO4. Preferably, it is KOH, K2CO3 or K2SO4. In an embodiment of the present invention, the bending strength of the chemically strengthened glass is ≥210 MPa. This indicates that the glass material of the present invention has good bending resistance. High bending strength means that the material has good anti-destruction performance under mechanical stress, prolongs service life, and adapts to various mechanical environment requirements.
[0054] In a fifth aspect of the present invention, a method for preparing the high-quality optoelectronic glass material with anti-glare function described in the fourth aspect is provided, comprising: a. Providing a light-transmitting glass substrate; b. performing a reduction treatment on the glass substrate in a reducing atmosphere to form a light absorbing layer on the surface of the light-transmitting glass substrate; c. performing secondary machining on the reduced glass substrate to remove part of the light absorbing layer to expose the light transmitting area; d. Chemically strengthen the glass after secondary machining to obtain a chemically strengthened optoelectronic glass material, which is a high-quality optoelectronic glass material with anti-glare function.
[0055] In an embodiment of the present invention, the light-transmitting glass substrate is as described in the third aspect above.
[0056] In some embodiments of the present invention, the reduction treatment is performed under a reducing atmosphere; the time of the reduction treatment is 5000-18000 min, the pressure is 0.01-0.3 MPa, and the temperature is 550-720°C.
[0057] In some embodiments of the present invention, the chemical strengthening includes placing the mixture in a salt bath for at least one chemical ion exchange, and the salt bath used for the ion exchange is selected from one or more molten salts of lithium salts, sodium salts and potassium salts.
[0058] In some embodiments of the present invention, the temperature during each chemical ion exchange is 350-540° C. and the time is 100-800 min.
[0059] In some embodiments of the present invention, the chemical strengthening is performed by two chemical ion exchanges, the first chemical ion exchange is performed in a salt bath of sodium salt, and the second chemical ion exchange is performed in a salt bath of potassium salt or a mixed salt of potassium salt and sodium salt.
[0060] In some embodiments of the present invention, during the chemical strengthening process, a catalyst may be added to the salt bath, and the amount of the catalyst added is 0-10 wt % of the total salt mass in the salt bath; preferably 5-10 wt %.
[0061] In some embodiments of the present invention, the catalyst is selected from one or more of KOH, KCl, K2CO3, Rb2CO3, KH2PO4, Ca(PO3)2, K3PO4 and K2SO4, preferably KOH, K2SO4 or K2CO3.
[0062] In the sixth aspect of the present invention, an optical element is provided, which is made of the high-quality optoelectronic glass material composition with anti-glare function described in the first aspect or the glass blank described in the second aspect, or contains the high-quality optoelectronic glass material with anti-glare function described in the fourth aspect.
[0063] In some embodiments of the present invention, the optical element is an optical input window.
[0064] In the seventh aspect of the present invention, a glass cover is provided, which is made of the high-quality optoelectronic glass material composition with anti-glare function described in the first aspect or the glass blank described in the second aspect, or includes the high-quality optoelectronic glass material with anti-glare function described in the fourth aspect.
[0065] In an eighth aspect of the present invention, a capacitive touch screen is provided, which is made of the high-quality optoelectronic glass material composition with anti-glare function described in the first aspect or the glass blank described in the second aspect, or includes the high-quality optoelectronic glass material with anti-glare function described in the fourth aspect.
[0066] In the ninth aspect of the present invention, there is provided the application of the high-quality optoelectronic glass material composition with anti-glare function described in the first aspect, or the glass blank described in the second aspect, or the high-quality optoelectronic glass material with anti-glare function described in the fourth aspect, or the optical element described in the sixth aspect in high-end optoelectronic detection and precision optical systems.
[0067] In some embodiments of the present invention, the above materials are used as optical input window materials in high-end photoelectric detection and precision optical systems.
[0068] In the tenth aspect of the present invention, there is provided application of the high-quality optoelectronic glass material composition with anti-glare function described in the first aspect, or the glass blank described in the second aspect, or the high-quality optoelectronic glass material with anti-glare function described in the fourth aspect, or the optical element described in the sixth aspect, or the glass cover plate described in the seventh aspect, or the capacitive touch screen described in the eighth aspect in consumer electronic devices, industrial and control systems, aerospace fields, energy fields and automotive electronics fields.
[0069] In some embodiments of the present invention, the consumer electronic devices are such as smartphones and tablet computers, where, for example, these materials are used as capacitive touch screens to provide touch input functions, allowing users to operate by touching the screen. For example, these materials are used as cover glass to protect the display screen and touch sensor from scratches and falls, and have anti-glare functions to improve visibility.
[0070] In some embodiments of the present invention, the industrial and control systems are used in industrial control displays and industrial control equipment, for example, where these materials are used as capacitive touch screens to provide an intuitive touch interface, allowing operators to directly interact with the equipment and improve operating efficiency. For example, these materials are used as cover glass to protect touch screens and displays, ensuring their durability and clarity in harsh environments, and are generally required to have impact resistance, scratch resistance, and anti-glare properties.
[0071] In some embodiments of the present invention, the aerospace field is used in aerospace equipment and flight displays, for example, where these materials are used as capacitive touch screens in navigation and control systems to provide pilots and operators with a convenient touch operation interface. For example, these materials are used as cover glass to protect flight displays and touch screens, ensuring their readability and durability in high brightness and high intensity environments, and having anti-glare and anti-reflection functions.
[0072] In some embodiments of the present invention, the energy field is, for example, in solar thermal photovoltaic power generation equipment, where, for example, these materials may be used as capacitive touch screens for monitoring and control interfaces, providing touch operation functions for device management and data monitoring. For example, these materials are used as cover glass: to protect touch screens and displays, ensuring their durability in outdoor environments, and anti-ultraviolet and anti-glare properties are particularly important.
[0073] In some embodiments of the present invention, the automotive electronics field is, for example, in vehicle display systems and navigation systems, where, for example, these materials are widely used as capacitive touch screens in vehicle infotainment systems and navigation systems to provide a touch operation interface for drivers and passengers. For example, these materials are used as cover glass to protect vehicle display screens and touch screens, ensuring their durability and clarity in the vehicle environment, and usually require anti-scratch and anti-glare properties.
[0074] The beneficial effects of the present invention are: The present invention provides a high-quality photoelectric glass material with anti-glare function, which has excellent spectral transmittance, and the spectral transmittance in the effective area is ≥90.00%@870 nm; it has good anti-halation and anti-crosstalk performance, and the transmittance of the light absorption layer is ≤1%@870 nm; it has good thermal properties, and the thermal expansion coefficient at 30-300℃ is (95-105)×10 -7 / ℃; glass transition temperature Tg≥540℃; sag temperature Ts≥630℃; has good bending resistance, the bending strength of the glass material after chemical strengthening is ≥210 MPa; has excellent glass internal quality, and the bubble degree meets the A0 level. These performance parameters jointly determine the overall quality and applicability of optoelectronic glass. High light transmittance, appropriate absorption layer thickness and low absorption layer transmittance ensure excellent optical performance; low thermal expansion coefficient, high glass transition temperature and sag temperature ensure thermal stability; high bending strength and low bubble degree ensure mechanical strength and internal purity. Combining these properties, the optoelectronic glass material of the present invention can fully meet the needs of high-end applications in terms of optical, thermal and mechanical properties, which makes it an ideal choice for optical input window materials, capacitive touch screens, and protective cover glass materials in high-end optoelectronic detection and precision optical systems. It can be widely used in various fields such as smart phones, tablets, IPADs, industrial control displays, aerospace, solar thermal photovoltaic power generation, and automotive. BRIEF DESCRIPTION OF THE DRAWINGS
[0075] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. The embodiments of the present invention are described in detail below in conjunction with the accompanying drawings, wherein: Figure 1 The thermal expansion coefficient curve of the glass of Example 3 of the present invention is shown.
[0076] Figure 2 A comparison chart of the effective area transmittance (@2 mm) and the absorption layer transmittance value (@870 nm) of Examples 1-6 of the present invention and Comparative Examples 1-10 before and after the glass reduction treatment is shown. DETAILED DESCRIPTION
[0077] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.
[0078] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. Unless otherwise specified, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions. In addition, any method and material similar to or equivalent to the described content can be applied to the method of the present invention. The preferred implementation methods and materials described in the text are for demonstration purposes only.
[0079] The invention provides a high-quality photoelectric glass material with an anti-glare function. The glass material comprises or has the following components, measured by mass percentage: 45-55% of SiO2, 0.1-3% of Bi2O3, 0-2% of PbO, 0.1-3% of In2O3, 0-3% of AgO, 0.1-2% of SnO2, 1-5% of Li2O, 8-16% of Na2O, 0-1% of K2O, 0-4% of B2O3, 10-18% of Al2O3, 1-8% of ZrO2, 1-3% of MgO, 1-4% of CaO, 0-1% of CeO2 and 0-2% of Sb2O3.
[0080] In particular, when the glass material of the present invention is composed of the above components, in some embodiments of the present invention, the glass material of the present invention has excellent spectral transmittance, the spectral transmittance in the effective area is ≥90.00%@870 nm; has good anti-halation and anti-crosstalk performance, the transmittance of the light absorption layer is ≤1%@870 nm; has good thermal properties, and the thermal expansion coefficient at 30-300°C is (95-105)×10 -7 / ℃; glass transition temperature Tg≥540℃; sag temperature Ts≥630℃; good bending resistance, the bending strength of the glass material after chemical strengthening is ≥210 MPa; excellent glass internal quality, and the bubble degree meets the A0 level. This makes it the preferred optical input window material in high-end photoelectric detection and precision optical systems, one of the key materials for capacitive touch screens, and also a protective cover glass. It is widely used in various fields such as smart phones, tablets, IPADs, industrial control displays, aerospace, solar thermal photovoltaic power generation, and automotive.
[0081] Furthermore, the present invention provides a method for preparing a photoelectric glass blank, which comprises: mixing the raw materials, melting them at a high temperature of 1520-1580°C, mechanically stirring them after melting, assisting bubbling clarification, then cooling them to 1350-1500°C for molding, and annealing them at 520-580°C after molding to obtain the photoelectric glass blank.
[0082] In some embodiments, the raw materials may also be selected from the following materials as needed: quartz sand, bismuth oxide (or bismuth nitrate pentahydrate), red lead (or yellow lead), indium oxide, silver nitrate, tin oxide, lithium carbonate, sodium carbonate (or sodium nitrate), potassium carbonate (or potassium nitrate), boron oxide (or boric acid), aluminum hydroxide (or aluminum oxide), zirconium oxide, magnesium oxide (or basic magnesium carbonate), calcium oxide (or calcium carbonate), cerium oxide and antimony oxide.
[0083] The above-mentioned optoelectronic glass blank is mechanically processed to obtain a light-transmitting glass substrate.
[0084] Furthermore, the present invention also provides a method for preparing a high-quality optoelectronic glass material with an anti-glare function, comprising: a. Providing a light-transmitting glass substrate; b. performing a reduction treatment on the glass substrate in a reducing atmosphere to form a light absorbing layer on the surface of the light-transmitting glass substrate; c. performing secondary machining on the reduced glass substrate to remove part of the light absorbing layer to expose the light transmitting area; d. Chemically strengthen the glass after secondary machining to obtain a chemically strengthened optoelectronic glass material, which is a high-quality optoelectronic glass material with anti-glare function.
[0085] The mechanical processing or secondary mechanical processing includes changing at least one of the physical form, surface quality and appearance of the glass blank. The physical form may be, for example, cutting the glass blank into a desired shape and size by cutting, or drilling a desired hole diameter and hole position on the glass blank by drilling. The surface quality may be, for example, improving the smoothness and transparency of the glass blank surface by polishing (for example, mechanical polishing), or grinding the glass edge by edge grinding to remove sharp edges and improve safety. The appearance may be, for example, making various patterns or logos on the surface of the glass blank by engraving (for example, mechanical engraving).
[0086] The reduction treatment is carried out in a reducing atmosphere, the reduction treatment time is 5000-18000 min, the pressure is 0.01-0.3 MPa, and the temperature is 550-720° C. The glass material with the absorption layer formed on the surface is mechanically processed.
[0087] Preferably, the machined material is chemically strengthened; the chemical strengthening refers to placing the glass in a salt bath for single or multiple chemical ion exchange, and the salt bath used for the ion exchange can be at least one of lithium salt, sodium salt and potassium salt; wherein the first chemical ion exchange is carried out in a sodium salt salt bath, and the second chemical ion exchange is carried out in a potassium salt or a mixed salt bath of potassium salt and sodium salt; during the first chemical strengthening process, the temperature during ion exchange is 350-540°C and the time is 100-800 min; during the second chemical strengthening process, the temperature during ion exchange is 350-540°C and the time is 10-800 min; In some embodiments, during the chemical strengthening process, a catalyst is added to the salt bath. The chemical strengthening process is accelerated by adding a catalyst. The catalyst is, for example, KOH, KCl, K2CO3, Rb2CO3, KH2PO4, Ca(PO3)2, K3PO4, K2SO4, or a mixture thereof. Specifically, the mass of the added catalyst is 0-10 wt% of the total mass of salt in the salt bath.
[0088] The method has process stability, and the glass material prepared by the process method can show stable characteristics, and will not cause non-negligible fluctuations in glass performance due to the increase or decrease of the process temperature within the range. Of course, it can be understood that within the process range, some higher temperatures can shorten the preparation process compared to lower temperatures. If it is necessary to shorten the time cost as much as possible, the technicians in this field can select a relatively higher temperature within the temperature range disclosed in the present invention when operating. If it is necessary to save energy as much as possible, the technicians in this field can also select a relatively lower temperature within the temperature range disclosed in the present invention when operating.
[0089] The present invention uses the following methods or standards to test the performance of glass: The transmittance of the glass sample was measured using a Shimadzu UV-Vis spectrophotometer (UV-3600Plus). The test wavelength range was 350 nm-1000 nm. The surface of the tested glass sample was optically polished and the thickness of the tested sample was 2 mm. (GB / T 7962.12-2010).
[0090] The thermal expansion coefficient of the glass sample was tested using the NETZSCH DIL 402 expansion coefficient tester. The glass sample was ground and polished into a cylindrical glass strip of Φ6 mm × 50 mm, and the two end faces were parallel. The instrument heating rate was set to 5 ℃ / min, and the data acquisition cycle was 20 ms. The data was plotted as a curve of the relationship between temperature and linear expansion, and the glass transition temperature (Tg) and expansion softening temperature (Tf) were obtained by the tangent method. The thermal expansion coefficient of optical glass refers to the elongation per unit length of the glass when the temperature rises by 1℃ within a certain temperature range. The sag temperature Ts refers to the temperature at which the glass sample stops expanding during the heating process. Optical glass will gradually change from a solid state to a plastic state in a certain temperature range. Its transition temperature Tg refers to the temperature corresponding to the intersection of the extension lines of the straight line parts of the low temperature area and the high temperature area when the glass sample is heated from room temperature to the sag temperature Ts. (GB / T7962.16-2010) The bending strength of the glass sample is measured using a three-point bending tester. The sample size is 3 mm × 4 mm × 40 mm. The four long sides of the tested glass sample are optically polished, the long edges are chamfered, and the end surface of the test sample does not require special treatment. (GB / T 6569-2006) The bubble density is defined as the volume per 100 cm 3 The degree of inclusions such as bubbles and stones contained in the glass, including their diameter and the total cross-sectional area of all bubbles, stones and other inclusions. (GB / T 7962.8-2010) Among them, the bubble degree A0 means that the total cross-sectional area of bubbles with a diameter of Φ≥0.05mm is >0.03-0.10 mm 2 / 100cm 2 ; The bubble degree A means that the total cross-sectional area of bubbles with a diameter of Φ≥0.05mm is >0.1-0.25 mm 2 / 100cm 2 ; Bubble degree B means that the total cross-sectional area of bubbles with diameter Φ≥0.05mm is >0.25-0.5 mm 2 / 100cm 2 .
[0091] Specifically, the embodiments and comparative examples of the present invention are carried out according to the above method, wherein the compositions of the glass samples of embodiments 1-6 and comparative examples 1-10 are shown in Table 1 and Table 2.
[0092] The preparation process parameters of the glass samples of Examples 1-6 and Comparative Examples 1-10 of the present invention are shown in Table 3.
[0093] The properties of the glass samples of Examples 1-6 and Comparative Examples 1-10 of the present invention are shown in Table 4 and Table 5.
[0094] The above results show that the optoelectronic glass material prepared in the embodiment of the present invention has excellent spectral transmittance, and its effective area spectral transmittance is ≥90.00%@870 nm, and has good anti-halation and anti-crosstalk performance. The transmittance of its light absorption layer is ≤1%@870 nm, and it has good thermal properties. Its thermal expansion coefficient at 30-300℃ is (95-105)×10 -7 / ℃, glass transition temperature Tg≥540℃, sag temperature Ts≥630℃, good bending resistance, bending strength of chemically strengthened glass material ≥210 MPa, excellent glass internal quality, and bubble degree meets A0 level. In addition, the operation of chemical strengthening treatment basically does not affect the spectral transmittance and thermal properties of the glass.
[0095] In addition, the present invention tests the glass properties of the same glass component (taking the glass composition of Example 3 as an example) under different blank preparation (see Table 6) or reduction treatment processes (see Table 7). The results show that the adjustment within the blank preparation and reduction treatment process range of the present invention can obtain a glass product with stable transmittance and thermal properties, whose effective area spectral transmittance is ≥90.00%@870 nm, the light absorption layer transmittance is ≤1%@870 nm, and its 30-300℃ thermal expansion coefficient is (95-105)×10 -7 / ℃, glass transition temperature Tg≥540℃, relaxation temperature Ts≥630℃.
[0096] Furthermore, the present invention takes the glass composition of Example 3 as an example, tests the preparation of optoelectronic glass materials with the same glass composition under the same blank preparation process and reduction treatment process conditions (see the blank preparation process and reduction treatment process parameters in Table 3), and then performs chemical strengthening treatment under different chemical strengthening preparation process parameters to prepare chemically strengthened optoelectronic glass. The chemical strengthening preparation process parameters and bending strength results are shown in Table 8.
[0097] Table 1 Composition of glass samples of Examples 1-6
[0098] Table 2 Composition of glass samples of Comparative Examples 1-10
[0099] Table 3 Glass sample preparation process of Examples 1-6 and Comparative Examples 1-10
[0100] Table 4 Performance test results of glass samples of Examples 1-6
[0101] Table 5 Performance test results of glass samples of comparative examples 1-10
[0102] Table 6 Billet preparation process parameters
[0103] Table 7 Reduction treatment process parameters
[0104] Table 8 Chemical strengthening treatment process parameters and test results
[0105] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A high-quality photoelectric glass material composition with anti-glare function, characterized in that: In terms of mass percentage, it contains the following components: 45-55% SiO2, 0.1-3% Bi2O3, 0-2% PbO, 0.1-3% In2O3, 0-3% AgO, 0.1-2% SnO2, 1-5% Li2O, 8-16% Na2O, 0-1% K2O, 0-4% B2O3, 10-18% Al2O3, 1-8% ZrO2, 1-3% MgO, 1-4% CaO, 0-1% CeO2 and 0-2% Sb2O3.
2. The high-quality optoelectronic glass material composition with anti-glare function according to claim 1, characterized in that: In terms of mass percentage, its composition includes: 45-55% SiO2, 0.1-3% Bi2O3, 0.5-2% PbO, 0.1-2% In2O3, 0-3% AgO, 0.1-2% SnO2, 1-5% Li2O, 8-16% Na2O, 0-1% K2O, 0-4% B2O3, 10-18% Al2O3, 1-8% ZrO2, 1-3% MgO, 1-4% CaO, 0-1% CeO2 and 0-2% Sb2O3; Preferably, the composition comprises, by mass percentage: 45-55% SiO2, 0.1-3% Bi2O3, 0.5-2% PbO, 1.5-3% In2O3, 0-3% AgO, 0.8-1.3% SnO2, 1-5% Li2O, 8-16% Na2O, 0-1% K2O, 0-4% B2O3, 10-18% Al2O3, 1-8% ZrO2, 1-3% MgO, 1-4% CaO, 0-1% CeO2 and 0-2% Sb2O3; Preferably, the composition comprises, by mass percentage, 45-55% SiO2, 0.1-3% Bi2O3, 0.5-2% PbO, 2-3% In2O3, 1-3% AgO, 0.8-1% SnO2, 1-2% Li2O, 8-16% Na2O, 0-1% K2O, 0-4% B2O3, 10-18% Al2O3, 1-8% ZrO2, 1-3% MgO, 1-4% CaO, 0-1% CeO2 and 0-2% Sb2O3; Preferably, its composition includes, by mass percentage, 45-55% SiO2, 0.1-3% Bi2O3, 0.5-2% PbO, 2-2.9% In2O3, 1.2-1.9% AgO, 0.1-2% SnO2, 1.1-2% Li2O, 8-16% Na2O, 0-1% K2O, 1-1.7% B2O3, 10-18% Al2O3, 1-8% ZrO2, 1-3% MgO, 1-4% CaO, 0-1% CeO2 and 1-2% Sb2O3.
3. A high-quality optoelectronic glass material composition with anti-glare function according to claim 1 or 2, characterized in that: In terms of mass percentage, the content of SiO2 is 49-55%, preferably 52-55%; Preferably, the content of Bi2O3 is 0.1-2.4% by mass, preferably 0.1-1%; Preferably, the content of PbO is 0 or 0.5-2%, preferably 1.5-2%, by mass percentage; Preferably, the content of In2O3 is 0.5-3%, preferably 1-3%, by mass percentage; Preferably, the content of AgO is 0 or 0.5-2%, preferably 01-1.2% by mass percentage; Preferably, the content of SnO2 is 0.5-1.3% by mass, preferably 0.8-1.3%; Preferably, the content of Li2O is 1-3%, preferably 1-2%, by mass percentage; Preferably, the content of Na2O is 8-15.2% by mass, preferably 10.7-16%; Preferably, the content of K2O is 0 or 0.1-1, preferably 0.5-0.8%, in terms of mass percentage; Preferably, the content of B2O3 is 0-3%, preferably 0 or 1-1.7%, by mass percentage; Preferably, the content of Al2O3 is 10-16% by mass, preferably 10-14%; Preferably, the content of ZrO2 is 1.1-8%, preferably 2.5-8%, by mass percentage; Preferably, the content of MgO is 1.2-3%, preferably 2.3-3%, by mass percentage; Preferably, the content of CaO is 2-4% by mass, preferably 2-3%; Preferably, the content of CeO2 is 0.1-1%, preferably 0.3-1%, by mass percentage; Preferably, the content of Sb2O3 is 0.1-2%, preferably 1-2%, by mass percentage.
4. A glass blank, which is prepared from the high-quality optoelectronic glass material composition with anti-glare function according to any one of claims 1 to 3; Preferably, the method for preparing the glass blank comprises: The raw materials are mixed and melted at a high temperature of 1520-1580°C. After melting, they are mechanically stirred and clarified by auxiliary bubbling. Then, the temperature is lowered to 1350-1500°C for molding. After molding, they are annealed at 520-580°C to obtain the product.
5. A light-transmitting glass substrate, which is prepared by mechanical processing of the glass blank according to claim 4; Preferably, the mechanical processing includes changing at least one of the physical form, surface quality and appearance of the glass blank; Preferably, the spectral transmittance of the light-transmitting glass substrate to 870 nm light is ≥90.00%.
6. A high-quality optoelectronic glass material with anti-glare function, comprising the light-transmitting glass substrate according to claim 5, and a light-absorbing layer arranged on the surface of the light-transmitting glass substrate; Preferably, the spectral transmittance of the light-transmitting glass substrate to 870nm light is ≥90.00%; the spectral transmittance of the light-absorbing layer to 870nm light is ≤1%; Preferably, the thickness of the light absorbing layer is ≥ 600 μm; Preferably, the light absorbing layer is produced on the surface of the light-transmitting glass substrate by reducing the light-transmitting glass substrate; Preferably, the reduction treatment is carried out under a reducing atmosphere, wherein: The reduction treatment time is 5000-18000 min, the pressure is 0.01-0.3 MPa, and the temperature is 550-720 °C; Preferably, the high-quality photoelectric glass material with anti-glare function is chemically strengthened glass, and the chemical strengthening comprises placing the high-quality photoelectric glass material with anti-glare function in a salt bath for at least one chemical ion exchange; Preferably, the temperature of each chemical ion exchange is 350-540°C and the time is 100-800 min; the salt bath is at least one salt selected from lithium salt, sodium salt and potassium salt; Preferably, the chemical strengthening is performed by two chemical ion exchanges, the first chemical strengthening is performed in a salt bath of sodium salt, and the second chemical strengthening is performed in a salt bath of potassium salt or a mixed salt of potassium salt and sodium salt; Preferably, during the chemical strengthening process, a catalyst may be added to the salt bath, and the amount of the catalyst added is 0-10 wt% of the total salt mass in the salt bath; Preferably, the catalyst is selected from one or more of KOH, KCl, K2CO3, Rb2CO3, KH2PO4, Ca(PO3)2, K3PO4 and K2SO4; Preferably, the high-quality photoelectric glass material with anti-glare function has a thermal expansion coefficient of (95-105)×10 -7 / ℃; glass transition temperature Tg≥540℃; relaxation temperature Ts≥630℃; Preferably, the bubble degree of the high-quality photoelectric glass material with anti-glare function meets the A0 level; Preferably, the bending strength of the chemically strengthened glass is ≥210 MPa.
7. A method for preparing the high-quality optoelectronic glass material with anti-glare function according to claim 5 or 6, comprising: a. Providing a light-transmitting glass substrate; b. performing a reduction treatment on the glass substrate in a reducing atmosphere to form a light absorbing layer on the surface of the light-transmitting glass substrate; c. performing a secondary mechanical treatment on the reduced glass substrate to remove part of the light absorbing layer to expose the light transmitting area; d. Chemically strengthening the glass after the secondary mechanical treatment to obtain a chemically strengthened optoelectronic glass material, which is a high-quality optoelectronic glass material with an anti-glare function; Preferably, the reduction treatment is carried out in a reducing atmosphere; the time of the reduction treatment is 5000-18000 min, the pressure is 0.01-0.3 MPa, and the temperature is 550-720 °C; Preferably, the chemical strengthening comprises placing the mixture in a salt bath for at least one chemical ion exchange, wherein the salt bath used for the ion exchange is selected from one or more molten salts of lithium salts, sodium salts and potassium salts; Preferably, the temperature during each chemical ion exchange is 350-540°C and the time is 100-800 min; Preferably, the chemical strengthening is carried out in a sodium salt bath for the first chemical strengthening and in a potassium salt or a mixed salt bath of potassium salt and sodium salt for the second chemical strengthening; Preferably, during the chemical strengthening process, a catalyst may be added to the salt bath, and the amount of the catalyst added is 0-10 wt% of the total salt mass in the salt bath; Preferably, the catalyst is selected from one or more of KOH, KCl, K2CO3, Rb2CO3, KH2PO4, Ca(PO3)2, K3PO4 and K2SO4.
8. An optical element, made of the high-quality optoelectronic glass material composition with anti-glare function according to any one of claims 1 to 3 or the glass blank according to claim 4, or comprising the high-quality optoelectronic glass material with anti-glare function according to claim 5 or 6; Preferably, the optical element is an optical input window.
9. Application of the high-quality optoelectronic glass material composition with anti-glare function according to any one of claims 1 to 3, or the glass blank according to claim 4, or the high-quality optoelectronic glass material with anti-glare function according to claim 5 or 6, or the optical element according to claim 8 in high-end optoelectronic detection and precision optical systems; Preferably, it is used as an optical input window material in high-end photoelectric detection and precision optical systems.
10. The use according to claim 9, characterized in that: The applications include the fields of consumer electronics, industrial and control systems, aerospace, energy and automotive electronics.
Citation Information
Patent Citations
Strengthened glass substrate manufacturing method and strengthened glass substrate
CN104114511A
Alkali-free aluminosilicate glass, composition for same, method for preparing alkali-free aluminosilicate glass and application thereof
CN105731790A
Glass article with blackened layer and method of making same
CN117088607A
High-strength anti-halation photoelectric glass material as well as preparation method and application thereof
CN118164672A
Strong stray light absorption anti-halation photoelectric glass as well as preparation method and application thereof
CN118221350A